(untitled) - Lubar, Steven (Washington, D.C., 2001)
As the authors demonstrate, views of history change over time, methods of historical investigation evolve and improve, and America's understanding of the past matures. Shifts in focus and attitude lie at the hearth of Legacies, which is organized around four concepts of what a national museum of history can be: a treasure house, a shrine to the famous, a palace of progress, and a mirror of the nation. Thus, the museum collects cherished or precious objects, houses celebrity memorabilia, documents technological advances, and reflects visitors' own lives. Taking examples from science and technology, politics, decorative arts, military history, ethnic heritage, popular culture and everyday life, the authors provide historical context for the work of the Smithsonian and shed new light on what is important, and who is included, in American history. Throughout its history, Lubar and Kendrick conclude, the museum has played a vital role in both shaping and reflecting America's sense of itself as a nation.
Keywords: Hiện vật văn hóa,Material culture; Sưu tập và bảo quản,Collection and preservation; Hoa Kỳ,United States